Principal Leadership: Efforts to Increase Teacher Competency in Darussalam Kindergarten Palangka Raya - Sardimi Sardimi; Niki Lisda (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The principal as the leader has responsibility for everything in the school, including teachers as teaching staff, of course the principal must be able to overcome problems related to teachers, in this case increasing teacher competence. So, the aim of this article is to analyze the planning and implementation of school principal programs in improving teacher competency. This research uses qualitative research. The data sources for this research are the principal and teachers at the Darussalam Palangka Raya Kindergarten. This research data collection technique uses interview, observation and documentation techniques. To ensure the validity of the data, researchers use source triangulation. Then the data was analyzed in four stages, namely data collection, data reduction, data display and data conclusions. Based on the research results, it shows that: first, school principals in planning programs to improve teacher competency have not been specifically formulated, but programs that have been implemented to improve teacher competency are contained in the principal's annual work program. The programs contained in the program are conducting RPP checks on teachers, checking teachers' attendance every day, checking teachers' administration every month. Second, the implementation of the program to improve teacher competency is carried out referring to the school principal's annual work program. Supervision is carried out once a year, and motivation is carried out when the principal and teachers hold a meeting which is usually held once a month. The principal also pays attention to the orderliness of teacher administration starting from the RPP and syllabus, where the principal checks every day for learning programs in lesson units, and checks teacher administration once a month from the beginning of the school year to the end of the school year